Don’t Reinvent the Wheel. Spin it for Advocacy - Knipe, Robert (Strategies, 2020)
This article expands previous recommendation to “be proactive” by providing practical examples that have the potential to encourage stakeholders to value HPE programs before these programs are threatened with reduction or elimination. The aim is to capitalize on positive aspects of programs that are already in place to maximize publicity within communities.
_eprint: https://doi.org/10.1080/08924562.2020.1805941
Keywords: dept.hms; peer-reviewed